Assessment of air flow distribution and hazardous release dispersion around a single obstacle using Reynolds-averaged Navier-Stokes equations - Vasilopoulos, Konstantinos; Sarris, Ioannis E.; Tsoutsanis, Panagiotis (Elsevier, 2019)
The flow around a cubical building, with a pollution source at the central point of the top of the cube, is studied. The Reynolds-averaged Navier-Stokes and species concentration equations are solved for Reynolds number, Re = 40,000, is based on the height of the cube. The predictions obtained with the standard, the Kato-Launder, and the low-Reynolds number k-epsilon models are examined with various wall functions for the near wall treatment of the flow. Results are compared against Martinuzzi and Tropea measurements (J. of Fluids Eng., 115, 85–92, 1993) for the flow field and against Li and Meroney (J. of Wind Eng. and Industrial Aerodynamics, 81, 333–345, 1983) experiments and Gaussian models for the concentration distribution. It is found that the present unstructured mesh model performs similarly to the structured mesh models. Results from the Kato-Launder model are closer to the experimental data for the flow patterns and contaminant distribution on the cube's roof. However, the Kato-Launder model has an over-prediction for the recirculation zone and the contaminant distribution windward of the cube. The standard k-epsilon and the low-Reynolds number k-epsilon models predict similar flow patterns and are closer to the experimental data of the cube's windward and side face.
Keywords: Environmental sciences; Mechanical engineering